Orange Pickeringite from the Algares 30-Level Adit, Aljustrel Mine, Iberian Pyrite Belt, Portugal - Silva, Teresa (2022)
ABSTRACT: The sheltered environment of the Algares +30 level adit (underground mine gallery) contributes to the preservation of secondary water-soluble minerals formed on the tunnel walls. The massive sulphide and related stockwork zone are hosted by the Mine Tuff volcanic unit and are exposed in the walls of the gallery, showing intense oxidation and hydrothermal alteration. Minerals from the halotrichite group were identified on the efflorescent salts, typically white fine-acicular crystals but also on aggregates with dark orange/brownish colour. Mineral characterization was performed using several methods and analytical techniques (XRD, XRF-WDS, SEM-EDS, DTA-TG), and the chemical formulas were calculated maintaining the ratio A:B ≅ 1:2 in accordance with the general formula of the halotrichite group, AB2(SO4)4·22H2O. This methodology allowed the assignment of the orange colour to the presence of trivalent iron on iron-rich pickeringite in partial substitution of aluminium.